Indonesian Gramatical Interference towards the Studentsâ Spoken and Written English - Pudiyono, Pudiyono (EDUCARE, 2012)
ABSTRACT: This research aimed to find out: (1) interference forms of Indonesian grammar towards the studentsâs spoken and written English competence; and (2) grammatical factors influencing grammatical Indonesian interference towards the studentsâs spoken and written English competence. The research method used was âmetode simak dan catatâ or observation and note taking mathod. This method was applied by notifying any expressions being interferenced from any academic activities. Therefore, the data were collected from studentsâ academic activities such as writing practices, reports, structured academic assignments, and also from discussion, seminars, and presentations. After the data had been collected and analyzed, they went into two main classifications. Those were sentencial interference (63.16%) and phrasal interference (36.84%). Further analyses showed that sentencial interfernce came into several sub-classifications such as the following: (1) sentence pattern S +Â Very + Verb + Object, 31.21%; (2) sentence pattern ofÂ Noun + Adjective, 12.2%; (3) sentence pattern of unapppropriate form, 6.57%; (4) sentence pattern of unintended or âketidaksengajaanâ, 5.3%; (5) impersonal it sentence pattern, 3.94%; and (6) active-passive sentence pattern, 3.94%. Meanwhile, phrasal interference came with 36.84% data and was classified into the following: (1) unorderly arrangement, 11.84%; (2) adverb formation, 5.3%; (3) inappropriate number, 9.2%; and (4) miscellaneous, 5%. Furthermore, the grammatical factor which influenced the Indonesian interference towards the English learning, both spoken and written, was the fact that the English language learners had little imposure and practice which made them difficult to internalize English linguistic knowledge they learned. KEY WODS: Sentencial interference, phrasal interference, linguistic environtment, grammatical patterns, acceptable patterns,âbahasaâ Indonesia, and English language.About the Author: Pudiyono, M.Hum. is a Lecturer at the Department of English Education, Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh, Purwokerto, Central Java, Indonesia. He can be reached at: pudiyono_12@yahoo.co.idHow to cite this article? Pudiyono. (2012). âIndonesian Gramatical Interference towards the Studentsâ Spoken and Written Englishâ in EDUCARE: International Journal for Educational Studies, Vol.4(2) February, pp.229-244. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 9, 2011); Revised (January 16, 2012); and Published (February 17, 2012).